Visual attention attraction and tourism review helpfulness – a new enhancing mechanism with profile pictures. Issue 12 (2nd December 2022) - Li, Hui; Li, Chunlin; Liang, Sai; Yang, Jing-jing
ABSTRACT: This study explores the mechanism of visual attention attraction effect of profile pictures on the review helpfulness. Firstly, it proposes two detailed influence mechanisms of visual attention in the tourism context to sharpen the theory of selective exposure and visual selective attention. Secondly, it identifies a new factor influencing the helpfulness of tourism reviews. Thirdly, this research presents insights regarding the heterogeneous impact of different profile pictures. The findings of this study provide an effective method to make the reviews more attractive and helpful. Our research provides implications for various groups in the tourism industry.